Preparation method of PDACN-Si photocatalytic hydrogen production catalyst
By introducing 2-aminothiophene-3-carbonitrile and silicon elements into the g-C3N4 photocatalyst, the PDACN-Si catalyst was prepared, which solved the problem of insufficient catalytic activity and stability of the existing g-C3N4 photocatalyst, and achieved significant results The effect of improving photocatalytic activity.
Patent Information
- Application Number
- CN202411636487.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-15
AI Technical Summary
The existing g-C3N4 photocatalysts have low utilization of visible light and fast photogenerated electron-hole recombination efficiency, resulting in insufficient catalytic activity and stability.
By copolymerizing 2-aminothiophene-3-forminnitrile with dicyandiamide, a combination of template method and microwave irradiation heating was used to prepare a PDACN-Si catalyst with a large-pore honeycomb structure to improve its photocatalytic activity.
The photocatalytic activity of PDACN-Si catalyst was significantly improved, and the rate of photocatalytic preparation of hydrogen reached 864.87 µmol h-1 g-1, which is 4.37 times that of unmodified carbon nitride, which enhances the practical application prospects of the catalyst.
Smart Images

Figure CN119425815A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of photocatalytic hydrogen production catalysts, and particularly relates to a PDACN-Si photocatalytic hydrogen production catalyst. Background Art
[0002] At present, my country is accelerating the transformation of energy utilization and vigorously improving energy utilization efficiency. Oil, gas and coal resources are stored underground, with high exploration and development costs, serious environmental pollution, and the more they are used, the less they are. However, "wind and light" resources are inexhaustible, all on the surface, with low exploration and development costs, and also have positive ecological effects. Therefore, the utilization and production of clean energy has attracted much attention from researchers.
[0003] Graphitic carbon nitride (g-C3N4) has attracted extensive attention because it is a stable, easy to synthesize, electronic band structure suitable for absorbing sunlight, easy to functionalize, and highly active and stable visible light catalyst. So far, molecules with high nitrogen content, represented by dicyandiamide, melamine and urea, have been routinely used as precursors for the production of g-C3N4. The precursor of g-C3N4 is obtained by calcination at high temperature (400 ~ 600℃) in air or inert atmosphere. During the polycondensation process of g-C3N4, these high nitrogen molecules can form various intermediates through several different reaction pathways. However, the problems of low visible light utilization and fast recombination efficiency of photogenerated electrons and holes in g-C3N4 still exist. Therefore, how to improve the visible light catalytic activity of g-C3N4 has become a hot research issue.
[0004] In the research of photocatalytic hydrogen production catalysts, the main research directions are to select appropriate precursors, find suitable synthesis methods, and then modify them to improve catalytic activity. Summary of the invention
[0005] The present invention takes into account the practical value of the g-C3N4 photocatalyst, the comprehensive catalytic effect and the shortcomings of the above-mentioned prior art, and provides a preparation method and application of a PDACN-Si photocatalytic hydrogen production catalyst to solve the problems of insufficient catalytic activity and stability of the g-C3N4 photocatalyst in the prior art and complex synthesis process. The obtained PDACN-Si catalyst is selected and debugged to have good practical application prospects.
[0006] The preparation method and application of a PDACN-Si photocatalytic hydrogen production catalyst described in the present invention include the following specific steps: A method for preparing a PDACN-Si photocatalytic hydrogen production catalyst comprises the following steps: Step 1: Disperse dicyandiamide in deionized water and stir until uniform to obtain a mixed solution; Step 2: dispersing silicon dioxide in the mixed solution in step 1, and stirring until uniform to obtain a mixed solution; Step 3: freeze-drying the mixed solution obtained in step 2 to remove water to obtain a white solid; Step 4: Place the white solid obtained in step 3 in a crucible, irradiate with microwaves to obtain a light yellow block, and grind it into a light yellow powder in a mortar; Step 5: Soak the yellow powder in step 4 in a sodium hydroxide solution, stir to dissolve the silicon dioxide, and obtain a yellow mixed solution; Step 6: Filter, wash, dry and collect the yellow mixed solution in step 5 to obtain a PDACN-Si catalyst.
[0007] Furthermore, 2-aminothiophene-3-carbonitrile is also added to the mixed solution in step 1.
[0008] More preferably, the mass ratio of dicyandiamide to 2-aminothiophene-3-carbonitrile in step 1 is (1.2 ~ 4):0.02.
[0009] Furthermore, the microwave irradiation method in step 4 is to put the white solid into a crucible, invert it in another crucible, fill the space between the two crucibles with insulation material, put the two sealed crucibles into an outer crucible filled with copper oxide powder, fill and seal with CuO, cover the crucible with a lid, and place it in the center of the microwave oven.
[0010] Furthermore, the parameters of the microwave irradiation in step 4 are power 500-600 W and time 20-30 min.
[0011] Furthermore, the concentration of NaOH in step 5 is 0 ~ 2 mol / L.
[0012] The PDACN-Si photocatalytic hydrogen production catalyst is obtained by the preparation method.
[0013] The PDACN-Si photocatalytic hydrogen production catalyst is used as a photocatalyst in photocatalytic preparation of hydrogen.
[0014] Compared with the prior art, the present invention has the following beneficial effects: In the present invention, (1) a self-doped sulfur source can be realized by copolymerizing 2-aminothiophene-3-carbonitrile with dicyandiamide, and a macroporous photocatalytic material can be simply prepared by using a template method and a microwave irradiation heating strategy. Dicyandiamide and 2-aminothiophene-3-carbonitrile are used as precursors, and microwave irradiation heating can be used to achieve rapid polymerization of the precursors, successfully doping sulfur elements into the catalyst, and synthesizing a catalyst with a macroporous honeycomb structure. By copolymerizing 2-aminothiophene-3-carbonitrile with dicyandiamide, sulfur-containing groups can be introduced into the structural framework of g-C3N4 to form sulfur-doped graphite phase carbon nitride with a high specific surface area. The photocatalyst synthesized in this way has good sheet fluffiness and dispersibility and high photocatalytic activity.
[0015] (2) The present invention uses SiO2 as a template to prepare a DACN-Si catalyst, and then uses NaOH to etch away the SiO2 in the catalyst, so that the obtained PDACN-Si catalyst forms a defective structure. The preparation method using SiO2 as a hard template makes the specific surface area of the PDACN-Si material higher, which is conducive to the exposure of more active sites, strengthens the electron transport and mass transfer process, and can adjust the size of the SiO2 hard template to achieve the adjustment of the catalyst surface pore size. The catalyst synthesized by this method can not only enhance the absorption of light, but also inhibit the recombination of electrons and holes. At the same time, it has a large specific surface area, which makes it have a higher photocatalytic activity.
[0016] (3) The catalyst preparation scheme involved in the present invention is a synthesis technology with adjustable catalyst morphology. In the present invention, microwave irradiation heating is used to replace the traditional muffle furnace / tube furnace high temperature heating process to synthesize graphite phase carbon nitride, and CuO is used as a microwave absorber. CuO can strongly and effectively absorb microwaves and can increase the temperature to 1285 K within 7 minutes, which can achieve rapid polymerization of the precursor. Compared with the traditional muffle furnace / tube furnace heating method, the carbon nitride material synthesized by the microwave irradiation heating process has higher crystallinity and a more obvious and single lamellar structure, and the lamellar structure of the graphite phase carbon nitride does not have block aggregation, which effectively enhances the specific surface area of the graphite phase carbon nitride. In addition, compared with muffle furnace / tube furnace heating, microwave irradiation heating requires less heating time, which greatly saves the synthesis cost and improves the preparation efficiency of the catalyst.
[0017] (4) The graphite phase carbon nitride obtained by copolymerization of 2-aminothiophene-3-carbonitrile and dicyandiamide involved in the present invention is prepared by a one-pot method and does not involve a complicated preparation process of catalytic secondary compounding. It is a simple and efficient method for preparing a photocatalyst.
[0018] (5) The PDACN-Si prepared by the preparation method described in the present invention is used as a photocatalyst material in the process of photocatalytic hydrogen production reaction. It exhibits excellent photocatalytic activity under experimental conditions. The hydrogen evolution rate under visible light irradiation (λ>420nm) reaches 864.87 µmol h -1 g -1 , which is 4.37 times that of the unmodified carbon nitride (DCN) sample, greatly improving the photocatalytic performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 A schematic diagram of a scanning electron microscope of PDACN-Si-100 prepared in Example 1; Figure 2 The X-ray diffraction patterns of Examples 1, 4, 5 and 6 are shown; Figure 3 Schematic diagram of the photocatalytic hydrogen production performance of PDACN-Si prepared in implementation cases 1, 2, and 3.
[0020] Figure 4 Schematic diagram of the photocatalytic hydrogen production performance of implementation cases 4, 5, and 6. DETAILED DESCRIPTION
[0021] The following is a clear and complete description of the technical solutions in the examples of the present invention. Obviously, the examples described are only part of the examples of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0022] The following experimental methods and detection methods are conventional methods unless otherwise specified; the following reagents and raw materials are commercially available unless otherwise specified.
[0023] Example 1 Step 1: Disperse 2 g of dicyandiamide and 20 mg of 2-aminothiophene-3-carbonitrile in 15 ml of deionized water, and stir magnetically until uniform to obtain a mixed solution; Step 2: Disperse 1 g of silicon dioxide (SiO2) in the mixed solution in step 1, and stir magnetically until a mixed solution is obtained; Step 3: freeze-drying the mixed solution obtained in step 2 to remove water to obtain a white solid; Step 4: The white solid obtained in step 3 was placed in a crucible and irradiated with microwaves at a power of 600 W for 30 min to obtain a light yellow block, which was then ground into a light yellow powder in a mortar; Step 5: Soak the yellow powder in step 4 in 100 ml, 2 mol / L sodium hydroxide (NaOH) solution and stir magnetically for 12 h to obtain a yellow mixed solution; Step 6: Filter, wash, dry and collect the yellow mixed solution in step 5 to obtain a PDACN-Si-100 catalyst.
[0024] Step 7: First, take 20 mg of PDACN-Si-100 photocatalyst, place it in a top-illuminated quartz reactor, add 18 mL of deionized water, and then measure 2 mL of 10 vol% triethanolamine as a sacrificial agent. Then, add a certain amount of H2PtCl6 to the resulting suspension, in-situ photodeposit Pt as a co-catalyst, where the mass fraction of Pt is 3%, and ultrasonicate for 3 min to fully disperse it to obtain a uniform suspension. Before using a xenon lamp for illumination, purge with ultrapure N2 for 20 min to remove the dissolved O2 in the water and achieve complete purification of the air in the reactor. Use a 300W xenon lamp and a UV cutoff filter (λ>420 nm) for photocatalytic reaction. The model of the xenon lamp is Beijing Bofeilai PLS-SXE 300, and the output light intensity is 100 mW cm -2 The product was analyzed by gas chromatograph (Shimadzu GC-2014, high purity nitrogen as carrier gas) equipped with a thermal conductivity detector and a 5A molecular sieve column. The product was extracted from the sealed reactor every hour for detection.
[0025] The photocatalytic performance of the PDACN-Si-100 catalyst prepared in this example was tested. Figure 2 As shown in Figure 2, the photocatalytic hydrogen production rate under the experimental conditions is 864.87 µmol•h -1 ·g -1 .
[0026] Example 2 Step 1: Disperse 1.2 g of dicyandiamide and 20 mg of 2-aminothiophene-3-carbonitrile in 15 ml of deionized water, and stir magnetically until uniform to obtain a mixed solution; Step 2: Disperse 1 g of silicon dioxide (SiO2) in the mixed solution in step 1, and stir magnetically until a mixed solution is obtained; Step 3: freeze-drying the mixed solution obtained in step 2 to remove water to obtain a white solid; Step 4: The white solid obtained in step 3 was placed in a crucible and irradiated with microwaves at a power of 600 W for 30 min to obtain a light yellow block, which was then ground into a light yellow powder in a mortar; Step 5: Soak the yellow powder in step 4 in 100 ml, 2 mol / L sodium hydroxide (NaOH) solution and stir magnetically for 12 h to obtain a yellow mixed solution; Step 6: Filter, wash, dry and collect the yellow mixed solution in step 5 to obtain a PDACN-Si-60 catalyst.
[0027] Step 7: First, take 20 mg of PDACN-Si-60 photocatalyst, place it in a top-illuminated quartz reactor, add 18 mL of deionized water, and then measure 2 mL of 10 vol% triethanolamine as a sacrificial agent. Then, add a certain amount of H2PtCl6 to the resulting suspension, in-situ photodeposit Pt as a co-catalyst, where the mass fraction of Pt is 3%, and ultrasonicate for 3 min to fully disperse it to obtain a uniform suspension. Before using a xenon lamp for illumination, purge with ultrapure N2 for 20 min to remove the dissolved O2 in the water and achieve complete purification of the air in the reactor. Use a 300W xenon lamp and a UV cutoff filter (λ>420 nm) for photocatalytic reaction. The model of the xenon lamp is Beijing Bofeilai PLS-SXE 300, and the output light intensity is 100 mW cm -2 The product was analyzed by gas chromatograph (Shimadzu GC-2014, high purity nitrogen as carrier gas) equipped with a thermal conductivity detector and a 5A molecular sieve column. The product was extracted from the sealed reactor every hour for detection.
[0028] Example 3 Step 1: Disperse 4 g of dicyandiamide and 20 mg of 2-aminothiophene-3-carbonitrile in 15 ml of deionized water, and stir magnetically until uniform to obtain a mixed solution; Step 2: Disperse 1 g of silicon dioxide (SiO2) in the mixed solution in step 1, and stir magnetically until a mixed solution is obtained; Step 3: freeze-drying the mixed solution obtained in step 2 to remove water to obtain a white solid; Step 4: The white solid obtained in step 3 was placed in a crucible, irradiated with microwaves at a power of 600 W to obtain a light yellow block, and ground into a light yellow powder in a mortar; Step 5: Soak the yellow powder in step 4 in 100 ml, 2 mol / L sodium hydroxide (NaOH) solution and stir magnetically for 12 h to obtain a yellow mixed solution; Step 6: Filter, wash, dry and collect the yellow mixed solution in step 5 to obtain a PDACN-Si-200 catalyst.
[0029] Step 7: First, take 20 mg of PDACN-Si-200 photocatalyst, place it in a top-illuminated quartz reactor, add 18 mL of deionized water, and then measure 2 mL of 10 vol% triethanolamine as a sacrificial agent. Then, add a certain amount of H2PtCl6 to the resulting suspension, in-situ photodeposit Pt as a co-catalyst, where the mass fraction of Pt is 3%, and ultrasonicate for 3 min to fully disperse it to obtain a uniform suspension. Before using a xenon lamp for illumination, purge with ultrapure N2 for 20 min to remove the dissolved O2 in the water and achieve complete purification of the air in the reactor. Use a 300W xenon lamp and a UV cutoff filter (λ>420 nm) for photocatalytic reaction. The model of the xenon lamp is Beijing Bofeilai PLS-SXE 300, and the output light intensity is 100 mW cm -2 The product was analyzed by gas chromatograph (Shimadzu GC-2014, high purity nitrogen as carrier gas) equipped with a thermal conductivity detector and a 5A molecular sieve column. The product was extracted from the sealed reactor every hour for detection.
[0030] Example 4 Step 1: Disperse 1.2 g of dicyandiamide in 15 ml of deionized water and stir magnetically until uniform to obtain a mixed solution; Step 2: freeze-drying the mixed solution obtained in step 1 to remove water to obtain a white solid; Step 3: The white solid obtained in step 2 was placed in a crucible and irradiated with microwaves at a power of 600 W for 30 min to obtain a light yellow block, which was then ground into a light yellow powder in a mortar to obtain a DCN catalyst.
[0031] Step 4: First, take 20 mg of DCN photocatalyst, place it in a top-illuminated quartz reactor, add 18 mL of deionized water, and then measure 2 mL of 10 vol% triethanolamine as a sacrificial agent. Then, add a certain amount of H2PtCl6 to the resulting suspension, and in-situ photodeposit Pt as a co-catalyst, where the mass fraction of Pt is 3%. Ultrasonicate for 3 min to fully disperse it to obtain a uniform suspension. Before using a xenon lamp for illumination, purge with ultrapure N2 for 20 min to remove the dissolved O2 in the water and achieve complete purification of the air in the reactor. Use a 300W xenon lamp and a UV cutoff filter (λ>420 nm) for photocatalytic reaction. The model of the xenon lamp is Beijing Bofeilai PLS-SXE 300, and the output light intensity is 100 mW cm -2 The product was analyzed by gas chromatograph (Shimadzu GC-2014, high purity nitrogen as carrier gas) equipped with a thermal conductivity detector and a 5A molecular sieve column. The product was extracted from the sealed reactor every hour for detection.
[0032] Example 5 Step 1: Disperse 1.2 g of dicyandiamide and 20 mg of 2-aminothiophene-3-carbonitrile in 15 ml of deionized water, and stir magnetically until uniform to obtain a mixed solution; Step 2: freeze-drying the mixed solution obtained in step 1 to remove water to obtain a white solid; Step 3: The white solid obtained in step 2 was placed in a crucible and irradiated with microwaves at a power of 600 W for 30 min to obtain a light yellow block, which was then ground into a light yellow powder in a mortar to obtain a DACN catalyst.
[0033] Step 4: First, take 20 mg of DACN photocatalyst, place it in a top-illuminated quartz reactor, add 18 mL of deionized water, and then measure 2 mL of 10 vol% triethanolamine as a sacrificial agent. Then, add a certain amount of H2PtCl6 to the resulting suspension, and in-situ photodeposit Pt as a co-catalyst, where the mass fraction of Pt is 3%. Ultrasonicate for 3 min to fully disperse it to obtain a uniform suspension. Before using a xenon lamp for illumination, purge with ultrapure N2 for 20 min to remove the dissolved O2 in the water and achieve complete purification of the air in the reactor. Use a 300W xenon lamp and a UV cutoff filter (λ>420 nm) for photocatalytic reaction. The model of the xenon lamp is Beijing Bofeilai PLS-SXE 300, and the output light intensity is 100 mW cm -2 The product was analyzed by gas chromatograph (Shimadzu GC-2014, high purity nitrogen as carrier gas) equipped with a thermal conductivity detector and a 5A molecular sieve column. The product was extracted from the sealed reactor every hour for detection.
[0034] Example 6 Step 1: Disperse 4 g of dicyandiamide and 20 mg of 2-aminothiophene-3-carbonitrile in 15 ml of deionized water, and stir magnetically until uniform to obtain a mixed solution; Step 2: Disperse 1 g of silicon dioxide (SiO2) in the mixed solution in step 1, and stir magnetically until a mixed solution is obtained; Step 3: freeze-drying the mixed solution obtained in step 2 to remove water to obtain a white solid; Step 4: The white solid obtained in step 3 was placed in a crucible, and microwaved at a power of 600 W to obtain a light yellow block, which was then ground into a light yellow powder in a mortar to obtain a DACN-Si catalyst; Step 7: First, take 20 mg of DACN-Si photocatalyst, place it in a top-illuminated quartz reactor, add 18 mL of deionized water, and then measure 2 mL of 10 vol% triethanolamine as a sacrificial agent. Then, add a certain amount of H2PtCl6 to the resulting suspension, in-situ photodeposit Pt as a co-catalyst, where the mass fraction of Pt is 3%, and ultrasonicate for 3 min to fully disperse it to obtain a uniform suspension. Before using a xenon lamp for illumination, purge with ultrapure N2 for 20 min to remove the dissolved O2 in the water and achieve complete purification of the air in the reactor. Use a 300W xenon lamp and a UV cutoff filter (λ>420 nm) for photocatalytic reaction. The model of the xenon lamp is Beijing Bofeilai PLS-SXE 300, and the output light intensity is 100 mW cm -2 The product was analyzed by gas chromatograph (Shimadzu GC-2014, high purity nitrogen as carrier gas) equipped with a thermal conductivity detector and a 5A molecular sieve column. The product was extracted from the sealed reactor every hour for detection.
[0035] The samples in Example 1 were characterized and tested, and the results showed that: See also Figure 1 , Figure 1 This is a scanning electron microscope image of the PDACN-Si-100 sample prepared in Example 1. From the image, it can be seen that the lamellar structure of the sample is not destroyed by etching the SiO2 hard template with NaOH, the lamellar layers become thinner, and all have obvious honeycomb-like macroporous structures.
[0036] See also Figure 2 , Figure 2 The X-ray diffraction patterns of the samples prepared in Examples 1, 4, 5 and 6 show that Examples 1, 4, 5 and 6 all show typical diffraction peaks of g-C3N4, indicating that carbon nitride can be obtained by thermal polycondensation of dicyandiamide and 2-aminothiophene-3-carbonitrile.
[0037] See also Figure 3 , Figure 3 Schematic diagram of the photocatalytic performance of the catalysts prepared in Examples 1, 2, and 3 of the present invention. It can be seen that the photocatalytic hydrogen production rates of the catalysts prepared in Examples 1, 2, and 3 are 864.87 µmol h -1 g -1 、508.125 µmol h -1 g -1 and 261.25 µmol h -1 g -1By etching the SiO2 hard template with NaOH to create large pores in the sample structure, and copolymerizing 2-aminothiophene-3-carbonitrile with dicyandiamide, the sulfur element was introduced into the sample structure framework, which significantly improved the photocatalytic performance of the sample.
[0038] See also Figure 4 , Figure 4 Schematic diagram of the photocatalytic performance of the catalysts prepared in Examples 4, 5, and 6 of the present invention. It can be seen that the photocatalytic hydrogen production rates of the catalysts prepared in Examples 4, 5, and 6 are 198.03 µmol h -1 g -1 、335.63 µmol h -1 g -1 and 345.78 µmol h -1 g -1 By comparing with Examples 1, 2, and 3, it is shown that the photocatalytic performance of the sample can be significantly improved by creating macropores in the sample structure and copolymerizing 2-aminothiophene-3-carbonitrile with dicyandiamide and introducing sulfur into the sample structure framework.
[0039] The above results show that the PDACN-Si photocatalyst of the present invention exhibits a fairly high level of photocatalytic activity under normal temperature and pressure conditions after photocatalytic hydrogen production performance test. The photocatalytic hydrogen production rate of the PDACN-Si catalyst prepared in Example 1 is 864.87 µmol h -1 g -1 , which is 4.37 times that of the unmodified carbon nitride (Example 4), greatly improving the photocatalytic activity of PDACN-Si.
[0040] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to specific details.
Claims
1. A method for preparing a PDACN-Si photocatalytic hydrogen production catalyst, characterized in that: The following steps are involved: Step 1: Disperse dicyandiamide in deionized water and stir until uniform to obtain a mixed solution; Step 2: dispersing silicon dioxide in the mixed solution in step 1, and stirring until uniform to obtain a mixed solution; Step 3: freeze-drying the mixed solution obtained in step 2 to remove water to obtain a white solid; Step 4: Place the white solid obtained in step 3 in a crucible, irradiate with microwaves to obtain a light yellow block, and grind it into a light yellow powder in a mortar; Step 5: Soak the yellow powder in step 4 in a sodium hydroxide solution, stir to dissolve the silicon dioxide, and obtain a yellow mixed solution; Step 6: Filter, wash, dry and collect the yellow mixed solution in step 5 to obtain a PDACN-Si catalyst.
2. The method for preparing the PDACN-Si photocatalytic hydrogen production catalyst according to claim 1, characterized in that: 2-aminothiophene-3-carbonitrile is also added to the mixed solution in step 1.
3. The method for preparing the PDACN-Si photocatalytic hydrogen production catalyst according to claim 2, characterized in that: The mass ratio of dicyandiamide to 2-aminothiophene-3-carbonitrile in step 1 is (1.2 ~ 4): 0.
02.
4. The method for preparing the PDACN-Si photocatalytic hydrogen production catalyst according to claim 1, characterized in that: The microwave irradiation method in step 4 is to put the white solid into a crucible, invert it in another crucible, fill the space between the two crucibles with insulation material, put the two sealed crucibles into an outer crucible filled with copper oxide powder, fill and seal with CuO, cover the crucible with a lid, and place it in the center of the microwave oven.
5. The method for preparing the PDACN-Si photocatalytic hydrogen production catalyst according to claim 1, characterized in that: The parameters of the microwave irradiation in step 4 are power 500-600 W and time 20-30 min.
6. The method for preparing the PDACN-Si photocatalytic hydrogen production catalyst according to claim 1, characterized in that: The NaOH concentration in step 5 is 0 ~ 2 mol / L.
Citation Information
Patent Citations
Copolymerization-modified graphite-phase carbon nitride hollow ball visible light-driven photocatalyst
CN103861630A
Preparation method of nitride carbon nanofibers and obtained product
CN105350113A
Preparation method and application of porous g-C3N4 material
CN109529908A